OSCILLATING INSTABILITY IN A FINITE SIZE CYLINDRICAL CHANNEL - Poyarkov, I.V. (Recent Contributions to Physics, 2017)
The problem of stability of mixing in a ternary isothermal mixture is solved for a finite-size diffusion channel using the perturbation method. We provide a comparative analysis between the positions of the oscillating stability line for a plane infinite layer and for ‘the mass permeability’ of a cylindrical channel of a finite size. Our theoretical results are in a good agreement with the experimental data obtained by the two-flasks method for the N2–0.333He+0.667Ar system.